Environmental resistance and habitat quality influence dispersal of the saltwater crocodile. Issue 4 (17th December 2021) - Fukuda, Yusuke; Moritz, Craig; Jang, Namchul; Webb, Grahame; Campbell, Hamish; Christian, Keith; Lindner, Garry; Banks, Sam
Abstract: Landscape genetics commonly focuses on the effects of environmental resistance on animal dispersal patterns, but there is an emerging focus on testing environmental effects on emigration and settlement choices. In this study, we used landscape genetics approaches to quantify dispersal patterns in the world's largest crocodilian, the saltwater crocodile ( Crocodylus porosus ), and demonstrated environmental influences on three processes that comprise dispersal: emigration, movement and settlement. We found that both environmental resistance and properties of the source and destination catchments (proportion of breeding habitat) were important factors influencing observed dispersal events. Our habitat quality variables related to hypotheses about resource competition and represented the ratio of breeding habitat (which limits carrying capacity), suggesting that competition for habitat influences emigration and settlement choices, together with the strong effect of environmental resistance to movement (where high‐quality habitat was associated with greatest environmental permeability). Approximately 42% of crocodiles were migrants from populations other than their sampling locations and some outstandingly productive populations had a much higher proportion of emigration rather than immigration. The distance most commonly travelled between source and destination was 150–200 km although a few travelled much longer distances, up to 600–700 km. Given the extensive dispersal range, individual catchments or hydrographic regions that combine two or three adjacent catchments are an appropriate scale for population management.